Evaluation of the Microbiota and Integrity of Respirators Reused by Health Professionals in a Hospital Environment - José D. Paiva; Giselda Neves; Paulo C. Neto; Wanuska Portugal; Douglas Ferreira; Fernando Lundgren; Idalina Cambuim; Ana C. Paiva; Elvis França (Aerosol and Air Quality Research)
Abstract The shortage of PFF2, N95, and KN95 respirators and their equivalents for the respiratory protection of the population and health professionals during COVID-19 pandemic has driven the adoption of alternative measures to address the lack of personal protective equipment (PPE). The use of surgical masks, handmade masks, and even the prolonged use of respirators were some of the measures adopted in response to the high demand for these products, and their consequent shortage. In this context, the present study evaluated the microbiota and integrity of reused PFF2 respirators in the central sterile services department of a hospital. Respirators that had been used for 0 h, 12 h, 24 h, and 36 h were sampled for the inoculation and cultivation of fungi and bacteria and the identification of their microbiota. To assess the integrity of the respirators, a filtration efficiency assessment test was conducted of the respirators used for 36 h. The results obtained showed that the microbiota of the respirators comprised commensal fungi and bacteria from the oral and nasal regions of human beings. It was also found that after 36 h of use, the respirators did not demonstrate a decrease in filtration efficiency; that is, they retained their 97% filtration efficiency. Considering the findings regarding the presence and pathogenicity of microorganisms, it is possible that the reuse of respirators for up to 36 h does not harm the health of immunocompetent users. In terms of PPE efficiency, no compromises were evidenced.